Back Cover: Direct Detection of Supramolecular Reaction Centers in the Methanol‐to‐Olefins Conversion over Zeolite H‐ZSM‐5 by 13C–27Al Solid‐State NMR Spectroscopy (Angew. Chem. Int. Ed. 7/2016). Issue 7 (14th January 2016) - Wang, Chao; Wang, Qiang; Xu, Jun; Qi, Guodong; Gao, Pan; Wang, Weiyu; Zou, Yunyun; Feng, Ningdong; Liu, Xiaolong; Deng, Feng
Abstract : Mechanistic understanding of hydrocarbon‐pool (HP) chemistry in the methanol‐to‐olefins conversion over zeolites is challenging. In their Communication onpage 2507 ff., F. Deng, J. Xu, and co‐workers report the direct detection of supramolecular reaction centers, composed of organic hydrocarbon‐pool species and the inorganic zeolite framework, by solid‐state NMR spectroscopy. The interaction/proximity between the hydrocarbon‐pool species and the Brønsted acid/base sites of the zeolite determines the reactivity of the hydrocarbon‐pool species.